Analisis Problematika Petani Kunyit Madura dan Alternatif Solusi - Maulidina Kusuma Wardani; Citra Nurhayati (Jurnal Ilmiah Membangun Desa dan Pertanian, 2023)
The purpose of this research was to highlight how turmeric farmers lived and to analyze all the problems they faced. Not only that, but we also tried to give alternative solutions that could help them grow. The research started in September 2021 when the pandemic was happening. This research was conducted using a qualitative and case study approach. Primary data sources, such as interviews and observations with turmeric farmers in Kajuanak village, and secondary data sources, such as a literature review, were used in this research. The result showed that they never got any help from stakeholders for all of this time. Besides that, they still use traditional methods and have a low sales rate. Based on these findings, we found some alternative solutions that could positively impact the growth of turmeric farmers. There is a synchronization of mission and vision, technology utilization training, how to use e-commerce courses, and providing funds and investment.